Pengendalian Hama pada Tanaman Sawi (Brassica juncea L.) Menggunakan Ekstrak Daun Pepaya (Carica papaya L.) - Tri Rima Setyawati, Noorbetha Julaily, Mukarlina (Universitas Tanjungpura, 2013)
Mustard (Brassica juncea L.) is a plant that quite popular and widely grown in West Kalimantan. The purpose of this study is to discover the concentration of papaya leaf extract (Carica papaya L.), as a pest controller in mustard (B. juncea L.) and investigate the effect of the intensity of pest attacks on mustard (B. juncea L.). The study was conducted around the greenhouse and the laboratory of Biology, Faculty of Mathematics and Natural Sciences University Tanjungpura, Pontianak in November 2011 to February 2012. The research used Completely Randomized Design consisting of 4 treatments and 2 controls (positive and negative) with 3 replications. Papaya leaf extract concentrations used were 25%, 50%, 75% and 100%. The results showed that pets that attack the mustard plant are crop controlling (Crocidolomia binotalis). The concentration of papaya leaf extract 100% was capable of controlling C. binotalis attack. 100% concentration showed the best results at the first week to the fourth week (0%), compared to a concentration of 25%, 50% and 75%. The use of papaya leaf extract 100% is a good number for of the mustard plant as a natural insecticide with number 10 strands of fresh mustard leaves, fresh weight, dry weight of 50.68 grams and 2.1 grams.